RETHINKING A NOTION OF THING IN PRIVATE LAW - Nikolic, Dusan (Zbornik radova Pravnog fakulteta u Novom Sadu, 2023)
In a rapidly changing World, changes in the field of law are inevitable, both at the theoretical level and in the domain of legal regulation. This, first of all, refers to basic doctrinal notions and legal definitions, which represent the basis for the construction and development of numerous legal institutes. In this context, a special place is occupied by the thing, as a starting category of property law that regulates relations related to the appropriation. In many legal systems, but also in legal doctrine, it is not entirely clear what and under what conditions can be appropriated. This is, on the one hand, a consequence of legal regulation lagging behind changes in society, and on the other, legal science lagging behind other scientific fields and overall technological development.From a legal point of view, a thing is still, in the spirit of attitudes developed in the 19th century, reduced to matter, although it has been proven that it is much more than that. From the point of view of fundamental sciences and modern integrative scientific disciplines of the new generation, everything in the human environment is made of matter, energy and information. Certain changes in the understanding of things occurred under the pressure of time and practical needs. Instead of meeting the changes, legal regulation and legal science react belatedly and intervene to what has been a part of reality for a long time. The gap between the normative and the real is alleviated by the fact that the other two elements of the Universe (energy and information) are also included under the traditional general notion of things (based on the thesis that thing is exclusively matter).
Keywords: Private Law; thing; notion; definition; matter; energy; information; virtual reality